Channel design for 3D models with applications in powder-bed additive manufacturing. Issue 9 (3rd April 2019) - Wei, Xiangzhi; Li, Xianda; Wen, Shanshan; Zheng, Yu; Tian, Yaobin
Abstract : Purpose: For any 3D model with chambers to be fabricated in powder-bed additive manufacturing processes such as SLM and SLS, powders are trapped in the chambers of the finished model. This paper aims to design a shortest network with the least number of outlets for efficiently leaking the trapped powders. Design/methodology/approach: This paper proposes a nonlinear objective with linear constraints for solving the channel design problem and a particle swarm optimization algorithm to solve the nonlinear system. Findings: Structural optimization for the channel network leads to fairly short channels in the interior of the 3D models and very few outlets on the model surface, which achieves the cleaning of the powders while causing almost the least changes to the model. Originality/value: This paper reveals the NP-harness of computing the shortest channel network with the least number of outlets. The proposed approach helps the design of lightweight models using the powder-bed additive manufacturing techniques.